2021
DOI: 10.15294/lc.v15i2.27787
|View full text |Cite
|
Sign up to set email alerts
|

Types of English Intensifiers on Social Media

Abstract: The use of English intensifiers keeps changing and flowing. It also varies according to the speaker’s background and style. Quirk, et.al (1992) divides intensifiers into emphasizers, amplifiers (maximizers, boosters), and downtoners (approximators, compromisers, diminishers, minimizers). This research aims to find out the types of English intensifiers on social media, specifically on Twitter. The most frequently used intensifiers are analyzed specifically to dig deeper into the social aspects in terms of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Previous studies also found that adjective intensification is the most common form of intensification produced by women. It also enriches the finding regarding male and female differences in vocabulary, which appealed that women highly produced intensifiers than men (Fuchs, 2017;Liebrecht et al, 2019;Sardabi & Afghari, 2015;Suryaningsih & Hardjanto, 2021).…”
Section: Benisupporting
confidence: 53%
See 2 more Smart Citations
“…Previous studies also found that adjective intensification is the most common form of intensification produced by women. It also enriches the finding regarding male and female differences in vocabulary, which appealed that women highly produced intensifiers than men (Fuchs, 2017;Liebrecht et al, 2019;Sardabi & Afghari, 2015;Suryaningsih & Hardjanto, 2021).…”
Section: Benisupporting
confidence: 53%
“…In describing the personality of Rani Maharani, Siti produced intensifiers twice in 'very kind and polite' and 'very impressive.' From this finding, intensifiers can be defined as a linguistic term for adverbs that modify the degree of another word, such as very and so (Liebrecht, Hustinx, & van Mulken, 2019;Sardabi & Afghari, 2015;Suryaningsih & Hardjanto, 2021). Hornby (1974)defines intensifiers as strengthening the meanings of the utterance, such as 'so,' 'very,' 'totally,' and 'awful.'…”
Section: Benimentioning
confidence: 99%
See 1 more Smart Citation